Assessing antimicrobial mechanisms in Langerhans cells during a Mycobacterium leprae infection - Fischbacher, Linda, author; Belisle, John, advisor; Gries, Casey, committee member; Tesfaye, Dawit, committee member (Colorado State University. Libraries, 2024)
Langerhans cells are essential immune cells in the skin that maintain homeostasis and clear pathogens. Despite their importance, much is unknown about Langerhans cells, including their innate antimicrobial mechanism. Single-cell sequencing of leprosy skin lesions identified genes upregulated in Langerhans cells of reversal reaction lesions that may be associated with antimicrobial activity. CCL22, MPEG1, and IDO1 were selected to study further as potential effectors in Langerhans cells for killing Mycobacterium leprae. We hypothesized that altered metabolic processes in Langerhans cells impact antimicrobial effects on M. leprae. An in vitro model was developed to induce antimicrobial gene expression in Langerhans cell-like dendritic cells (LCDCs). IL-1β was identified as the best inducer of CCL22 and MPEG1, and IFN-γ as the best inducer of IDO1. Induction was measured by gene expression and protein production, as well as enzyme activity for IDO1 by measuring metabolites. The antimicrobial effect of IDO1 on intracellular M. leprae in LCDCs was assessed by inducing IDO1 with IFN-γ or inhibiting IDO1 activity with 1-methyltryptophan. Stimulation by this agonist or this antagonist modulated IDO1 expression and activity but did not affect M. leprae viability. The changes of intracellular tryptophan catabolites in non-stimulated and M. leprae-infected LCDCs were measured. The M. leprae infection increased two kynurenine pathway catabolites after 24 and 48 hours, 3-hydroxyanthranilic acid and quinolinic acid. These data indicate that while M. leprae did not induce IDO1 expression, it did increase IDO1 and kynurenine pathway activity. Neither metabolite has reported antimicrobial properties, but quinolinic acid may benefit M. leprae for synthesizing nicotinamide adenine dinucleotide. A different tryptophan catabolite pathway leads to serotonin production. In M. leprae-infected LCDCs, serotonin was decreased, but 5-hydroxyindoleacetic acid, a breakdown product of serotonin, was increased. The implication of these changes for an M. leprae infection of LCDCs is unknown. 5-hydroxyindoleacetic acid is also increased in Mycobacterium tuberculosis patients. This metabolite may benefit these mycobacteria as it is reported to increase PPARγ activity, which is known to support M. leprae and M. tuberculosis in macrophages. The main antimicrobial mechanism of IDO1 is depleting tryptophan from tryptophan auxotrophic pathogens. Whether the tryptophan biosynthesis pathway in M. leprae is functional was assessed using 13C-tracing, to determine if tryptophan depletion by IDO1 could kill M. leprae. In axenic media, M. leprae did not synthesize tryptophan from 13C-glucose and 13C-palmitic acid nor synthesize tryptophan from intracellular 13C-glucose. In vitro, M. leprae only synthesized tryptophan from an intermediate, anthranilic acid. Using the same method, M. tuberculosis synthesis of tryptophan from 13C-glucose was confirmed as a control. The functionality of the tryptophan biosynthesis pathway in M. leprae could not be confirmed. However, because of the homology between the M. leprae and M. tuberculosis genes for tryptophan biosynthesis, this pathway likely is functional, and M. leprae would not be killed by IDO1-mediated tryptophan depletion. These findings indicate that IDO1 is not associated with antimicrobial activity towards M. leprae in LCDCs. Instead, increased IDO1 activity induced by M. leprae infection resulted in increased tryptophan catabolites likely to benefit rather than kill M. leprae in LCDCs. M. leprae likely evades the primary killing mechanism of IDO1, tryptophan depletion, by possessing an intact pathway for tryptophan biosynthesis. Further studies to elucidate the importance of quinolinic acid and 5-hydroxyindoleactic acid for M. leprae and validate that the M. leprae tryptophan biosynthesis pathway is functional will aid in identifying essential pathways for M. leprae that can be targeted with therapeutics. Other potential antimicrobial effectors in LCDCs, including CCL22 and MPEG1, will need to be assessed to study this innate mechanism in Langerhans cells further.
Keywords: IDO1; metabolism; tryptophan; Langerhans cells; antimicrobial mechanisms; Mycobacterium leprae